Answer:
its C
Step-by-step explanation:
Answer:
5+90m
Step-by-step explanation:
117 - 78m + 168m - 112
117- 112 = 5
-78m + 168m= 90m
5+90m
Answer:
x = 0, y = 1
Step-by-step explanation:
2x + 6y = 6 → (1)
x - 3y = - 3 ( add 3y to both sides )
x = 3y - 3 → (2)
substitute x = 3y - 3 into (1)
2(3y - 3) + 6y = 6 ← distribute parenthesis and simplify left side
6y - 6 + 6y = 6
12y - 6 = 6 ( add 6 to both sides )
12y = 12 ( divide both sides by 12 )
y = 1
substitute y = 1 into (2)
x = 3(1) - 3 = 3 - 3 = 0
solution is x = 0 , y = 1
The function f(x) - g(x) is an illustration of a composite function
Leanne's end result of f(x) - g(x) = -1/2x + 9 is correct
<h3>How to estimate the student's answer?</h3>
The functions are given as:
f(x) = 1/2x + 6
g(x) = x - 3
The function f(x) - g(x) is calculated using:
f(x) - g(x) = 1/2x + 6 - x + 3
Collect like terms
f(x) - g(x) = 1/2x - x + 6 + 3
Evaluate the like terms
f(x) - g(x) = -1/2x + 9
By comparing the above solution to the students' response, we can see that:
Leanne's end result of f(x) - g(x) = -1/2x + 9 is correct
Read more about composite functions at:
brainly.com/question/13502804